Preparation and characterization of TiO2-PEG NPs loaded doxorubicin - Zahra Sobhani; Reyhaneh Khademi; Mohammad Ali Behnam; Amin Reza Akbarizadeh (Shiraz University of Medical Sciences, 2019)
Many chemotherapeutics used for cancer treatments show systemic toxicity to the normal tissues. Using nanoparticles (NPs) improves drug delivery efficiency and decreases the side effects. The aim of this study was to load doxorubicin (DOX) on TiO2 NPs for its potential role in enhancing the anticancer efficacy of DOX while reducing its side effects. At first, for improving the dispersibility of TiO2 NPs in water, the polyethylene glycol (PEG) with two MWs (1000 and 4000 kDa) was used for wrapping the surface of TiO2 NPs. DOX was loaded on the TiO2 NPs by forming complexes with titanium, to construct TiO2-PEG-DOX NPs. The effects of various weight ratios of DOX to TiO2 on the loading efficiencies of NPs were assessed. The stability of these NPs in 2 different pH values (7.4 and 5) was evaluated. At the end, the cytotoxicity of TiO2-PEG-DOX was compared with free DOX against MCF-7 cell line. The formation of a thin layer of PEG around the TiO2 NPs was confirmed through thermo gravimetric analysis and transmission electron microscopy techniques. Fluorescence scanning results showed the complex formation between DOX and TiO2-PEG. The loading efficiency of DOX in TiO2-PEG1000 was 74% and in TiO2-PEG4000 was up to 85%. These complexes were stable at different pH values for long time (one month). The viability percent of cancerous cells expose to TiO2-PEG-DOX was lower than free DOX after 48 hours. The characteristics of TiO2-PEG-DOX show that this drug delivery system is a promising strategy for future clinical practice.